2022
DOI: 10.3389/fphys.2022.1004714
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose norepinephrine in combination with hypotensive resuscitation may prolong the golden window for uncontrolled hemorrhagic shock in rats

Abstract: Hypotension resuscitation is an important principle for the treatment after trauma. Current hypotensive resuscitation strategies cannot obtain an ideal outcome for remote regions. With the uncontrolled hemorrhagic shock (UHS) model in rats, the effects of norepinephrine (NE) on the tolerance time of hypotensive resuscitation, blood loss, vital organ functions, and animal survival were observed. Before bleeding was controlled, only the LR infusion could effectively maintain the MAP to 50–60 mmHg for 1 h, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…NE is the first-line treatment for maintaining end-organ perfusion pressure, particularly in critically ill patients with low systemic vascular resistance ( Chen et al, 2020 ), as it can effectively elevate arterial blood pressure through exerting pharmacological effects on α 1 adrenoceptors ( Zhou et al, 2022 ). Davis (1992) reported that when blood pressure was increased to 140 mm Hg, NE did not significantly affect the lumen cross-sectional area and cause any vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…NE is the first-line treatment for maintaining end-organ perfusion pressure, particularly in critically ill patients with low systemic vascular resistance ( Chen et al, 2020 ), as it can effectively elevate arterial blood pressure through exerting pharmacological effects on α 1 adrenoceptors ( Zhou et al, 2022 ). Davis (1992) reported that when blood pressure was increased to 140 mm Hg, NE did not significantly affect the lumen cross-sectional area and cause any vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%